واقع التدريس وفق المقاربة بالكفاءات في المنظومة التربوية الجزائرية - كروم, العايزة; كروم, خميستى (جامعة الوادي - University of Eloued, 2022)
إن مساهمة الفرد في بناء المجتمع خطوة مهمة، لكن الأهم هو تدخل قطاع التربية والتعليم في إعداده وتزويده بالكفاءات والمهارات التي تمكنه من مواجهة مختلف الوضعيات والمواقف الحياتية. وهنا يأتي دور المدرسة التي يفترض تحويل مساعيها إلى ممارسة فعلية، من خلال وضع مناهج دراسية تتماشى مع المستجدات والتغيرات الحاصلة. وفي هذا السياق تبنت المنظومة التربوية الجزائرية مجموعة من الإصلاحات وأدخلت مقاربة التدريس بالكفاءات، تلك المقاربة ذات النظرة البعيدة لطرق التدريس وأنشطة التعليم وأسس التقييم والتقويم. وعليه فإننا في هذا المقال سنركز على واقع التدريس وفق المقاربة بالكفاءات في المنظومة التربوية الجزائرية. The individual’s contribution to building society is an important step, but the most important thing is the intervention of the education sector in preparing it and providing it with the competencies and skills that enable it to face various life situations and situations. Here comes the role of the school, whose endeavors are supposed to be transformed into an actual practice, by developing curricula that are in line with the developments and changes taking place. In this context, the Algerian educational system has adopted a set of reforms and introduced the approach of teaching with competencies, that approach with a far view of teaching methods, teaching activities, and the foundations of evaluation and evaluation. Therefore, in this article we will focus on teaching according to the approach with competencies in the Algerian educational system
مقال
Keywords: المقاربة؛ التدريس بالكفاءات؛ المنظومة التربوية; Approach; Teaching with competencies; the educational system